ANALISIS DAMPAK DEVALUASI MATA UANG YUAN CHINA TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN YANG LISTING DI BURSA EFEK INDONESIA - Amir Kusnanto (Adbis: Jurnal Administrasi dan Bisnis, 2017)
Devaluation Yuan affect the global economy, this can be seen with the decline in currency exchange rates and falling stock prices in many countries. Based on this background, the authors do research event study. The selected time period is 11 days of exchange as the event period separated to 5 days before the event day (11 August 2015 as event day) and 5 days after the event day. The results showed that (1) by calculating the average abnormal return (AAR) is known to have a positive abnormal return during the event period; (2) different test results with paired sample test there is no significant difference of average abnormal return between before and after devaluation of Chinese Yuan currency; And (3) with different test using paired sample test there is no significant difference of average trading volume activity between before and after devaluation of Yuan Chinese currency.